Food tables & labelling - Bender, Arnold E. [ (Arnold Eric)]; Bender, David A. (Oxford University Press, 1998)
Students of all levels studying home economics, food technology, chemistry, biology, or any subject that involves nutrition and food science will find Food Tables and Labelling an invaluable resource